Suitability of ‘Guidelines for screening of prosthetic candidates: lower limb’ for Eastern Cape - Mduzana, Luphiwo Lakhanya (Stellenbosch : Stellenbosch University, 2017)
Thesis (MHumanRehabSt)--Stellenbosch University, 2017.